Ontologi Laba: Dari Angka Akuntansi ke Realitas Sosial - Muhammad Faiz Hardiansyah; Syahriar Abdullah (Jurnal Ilmiah Aset, 2026)
This paper examines the ontological status of profit in accounting by addressing a fundamental philosophical question: does profit exist as an objective economic reality, or is it primarily a social construct produced through accounting practices? Using a qualitative literature review, this study synthesizes seminal and recent accounting scholarship on realism, interpretivism, performativity, and critical realism. The analysis shows that profit cannot be understood solely as a neutral reflection of underlying economic facts. Rather, profit is shaped by accounting conventions, institutional settings, and social interpretations that determine how economic events are recognized, measured, and communicated. At the same time, profit is not merely fictional, because once reported, trusted, and used, it produces real consequences for managerial decisions, investor judgments, organizational legitimacy, and public policy. Thus, profit should be understood as a conceptually constructed yet socially real phenomenon with performative and causal effects. This ontological perspective broadens the role of accounting from a technical measurement tool to a social mechanism that participates in shaping economic reality, accountability, and power relations in contemporary society.